Tetillidae (Spirophorida, Porifera): a taxonomic reevaluation - Rützler, K (In: Vacelet J, Boury-Esnault N (eds) Taxonomy of Porifera from the N.E. Atlantic and the Mediterranean Sea. NATO Advanced Science Institutes Series G, Ecological Sciences volume 13. Springer, Heidelberg, pp 187-203, 1987)
A large series of tetillid sponges was analysed using museum specimens and live material. The study led to areevaluation of genera in that fami- ly, as well as of characters used to distinguish species. Properties of cor- tex, porocalices, and unusual accessory spicules are deemed adequate for distinguishing seven genera at the present state of our knowledge : Tetilla, Craniella, Cinachyra, Paratetilla, Amphitethya, Cinachyrella, (elevated from subgeneric status), and Acanthotetilla. Only few traditional species charac- teristics are considered stable enough to allow separating western Atlantic Cinachyrella. These apply to five species : C. alloclada, C. kuekenthali, C. tarentina, C. apion, and C. new species (van Soest &Stentoft, in press). It is recommended to avoid descriptions of new species without representative specimen series and observations of live populations, and to examine addi- tional biological and molecular biological properties of the sponges for possible application in taxonomy.
Proceedings of the 2nd Workshop on Atlanto-Mediterranean Sponge Taxonomy